The Destabilizing Effect of Glacial Unloading on a Large Volcanic Slope Instability in Southeast Iceland - Daniel Ben-Yehoshua; Sigurður Erlingsson; Þorsteinn Sæmundsson; Reginald L. Hermanns; Eyjólfur Magnússon; Robert A. Askew; Jóhann Helgason (GeoHazards)
Since the turn of the 20th century, glacial thinning has been exposing volcanic mountain slopes around Iceland’s outlet glaciers. In the early 2000s, several slope instabilities appeared around the Svínafellsjökull outlet glacier in Southeast Iceland. The largest of these is located on a slope called Svarthamrar and is defined by a more than 2 km-long fracture system that separates the northernmost part of the mountain, south of Svínafellsjökull. Here we present updated glacier bed topography, a stratigraphical and structural assessment of the Svarthamrar slope, and quantify the destabilizing effect of glacial unloading from 1890 to deglaciated. Our results show that the slope was predisposed to instability by structural discontinuities and a strongly overdeepened glacial trough. Glacial unloading likely controlled the slope destabilization, potentially exacerbated by temporarily steeper hydraulic gradients due to rapid glacier thinning in the late 1990s and 2000s. The load of older landslide deposits on the glacier acts stabilizing on the slope. We propose that future glacial thinning will reduce the slope stability further, making it more susceptible to external triggers, and resulting in reactivation of the deformation and potential failure. Similar trends of destabilization can be expected for many slopes in Iceland and elsewhere.